Distúrbios respiratórios durante o sono em crianças e adolescentes com sobrepeso, obesidade e roncos - Eliazor Campos Caixeta (2004)
A century after William Hill, in 1889, had clearly described the classic clinical picture of children with sleep apnea, Gastaut in 1966 described for the first time the blockage of the upper airways in adults during sleep, studying the manifestations of the Pickwick Syndrome. Guillerminault et al. published an article in 1976, with eight children with ObstructiveSleep Apnea Syndrome (OSAS). The first studies involving obese children had been carried through in 80´s decade by Mallory. From morbid obese, the author described 10 times more prevalent, than in children´s population in general. Snores are the main markers of the obstructive sleep apnea. However, frequently are forgotten and don´t receive due attention from the parents and health professionals. As result,there is a delay in diagnosis, and child is admitted with findings of proteinúria, enuresis, disturb of behavior, aggressiveness, capacity of deficient learning, difficulties in the school, or some times with cor-pulmonale. Although the subject is not new, we observe in this small historical report that only in the last 20 years, the clinical and therapeutical bases was established clearly. The present study seiks to evaluate the respiratory disturbances of sleep, in population children with overweight and obesity of the metropolitan region of Belo Horizonte city, Southern of Brazil, treated in the Clinic of Nutrition of the Clinical Hospital, FederalUniversity of Minas Gerais (HC/UFMG). Snoring is an important marker of the respiratory disturbance of sleep. Thirty (30) children and adolescents aged between 4 and 18 years old, snoring and weight excess had been studied, and the prevalence of OSAHS and its polysomnographic,anthropometrics and clinical findings was compared. In this manner it can contribute in the suspicious diagnosis and serve to alert the health professionals. Those with a background of surgical intervention in upper airways were excluded. A questionnaire was applied, to identify signals and symptoms of sleep respiratory disturbs, besides specific clinical evaluations, anthropometrics measures, polisomnographic andbioimpedance. Nutritional evaluation was made through the EpiNut subprogram of software Epi-info version 2002. The statistical analyses, had obeyed the classic methods of variable comparison. When the changeable answers had been considered as continuous, the Pearson coefficient of correlation was used. Considering the variable reply as continuous, distribution of the dichotomies variable was carried through a comparison of the averages of these according to.To verify if the variance of the continuous, corresponding variable to the qui-square of theshunting line-standard, it was homogeneous among the two groups of each dichotomies variable was used the qui-square of Bartlett, calculated by EpiInfo. This indicates that the variances are homogeneous when presents value of p > 0, 05. In this case those parametric tests had been used as "ANOVA" (Analysis of Variance) and "t" test. The results had demonstrated a prevalence of 93% of sleep apnea disturbance inchildren and adolescents with overweight, obesity and snores. However, it did not have a significant statistics correlation, when compared to the variable reply with signals and clinical symptoms, or the findings of physical examination such as, neck circumference, waist/hip relation and others. The only dependent variable that demonstrated a strong correlation with the variable reply was the allergic rhinitis. It is in agreement with literature findings. The sample size of the present study, may also have contributed to its results. For a better evaluation, appropriate statistical methods for projection and orientation of new studies had been used. With time elapsing and a big number of studies, diagnostic facilities may be found. In conclusion, it becomes difficult to differentiate exclusively through the clinical findings, children with or without apnea. However, children with weight excess and snoring,especially those with clinical history of allergic rhinitis will have to be checked to respirtory sleep disturbance. The reality, is that we dont have a safe form to identify OSAHS in children, without submitting them to polisomnographic